2007
DOI: 10.1089/vim.2006.0090
|View full text |Cite
|
Sign up to set email alerts
|

Restricted and Selective Tropism of a Venezuelan Equine Encephalitis Virus-Derived Replicon Vector for Human Dendritic Cells

Abstract: Dendritic cells (DCs) consist of heterogeneous phenotypic populations and have diverse immunostimulatory functions dependent on both lineage and functional phenotype, but as exceptionally potent antigen-presenting cells, they are targets for generating effective antigen-specific immune responses. A promising replicon particle vector derived from Venezuelan equine encephalitis virus (VEE) has been reported to transduce murine footpad DCs. However, the receptive DC subset, the degree of restriction for this trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 80 publications
1
35
0
Order By: Relevance
“…Given that dendritic cells are phenotypically heterogeneous, the exact type of dendritic cells infected in vivo remains to be determined. That alphaviruses can infect dendritic cells has been reported for RRV, Sindbis, and Venezuelan equine encephalitis viruses (61)(62)(63).…”
Section: Figurementioning
confidence: 82%
“…Given that dendritic cells are phenotypically heterogeneous, the exact type of dendritic cells infected in vivo remains to be determined. That alphaviruses can infect dendritic cells has been reported for RRV, Sindbis, and Venezuelan equine encephalitis viruses (61)(62)(63).…”
Section: Figurementioning
confidence: 82%
“…The VRP, VSV, and adenovirus-based vaccines are the only filovirus vaccine candidates to provide full protection to NHPs after only one vaccination (19,41,42). Potency associated with the VRP-based vaccines may be partially attributed to the propensity of VRPs to infect antigen-presenting cells, in particular, dendritic cells (43). Natural adjuvant properties of VRPs are known to promote antigen-specific T cell immunity and regulate a balanced antigen specific antibody response, which may also contribute to the potency of the VRP vaccine platform (44).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, GVI3000 particles can migrate directly to DLNs, where they preferentially target DCs (36,37). In both human-and mouse-derived DCs, in vitro studies have shown an upregulation of costimulatory molecules as well as secretion of proinflammatory cytokines, such as type I IFN, IL-6, and TNF after infection (37)(38)(39). In adult mice, cytokine secretion was observed systemically and in the DLNs as soon as 6 h after GVI3000 inoculation (unpublished observation).…”
mentioning
confidence: 93%